PERCEPTION OF STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS ON THE IMPACT OF THE APPLICATION OF BLOCKCHAIN TECHNOLOGY ON THE ACCOUNTING PROFESSION - Diwanni, Feby; Novitasari, Yuli; Ali Muhammad (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
The development of digital technology, especially blockchain technology, has brought significant changes to the practice and role of the accounting profession, thus demanding adequate human resource readiness. This study aims to analyze the perception of students of the Faculty of Economics and Business, majoring in accounting and management on the impact of the application of blockchain technology on the accounting profession by reviewing the influence of knowledge and skills on student awareness. This study uses a quantitative approach with a survey method through the distribution of questionnaires to 205 students of the Faculty of Economics and Business, majoring in accounting and management at the University of Science Indonesia who were selected using purposive sampling techniques. The data were analyzed using multiple linear regression with the help of SPSS software, accompanied by validity, reliability, and classical assumption tests. The results of the study show that students' knowledge and skills have a positive and significant effect on awareness about the application of blockchain technology in the accounting profession, both partially and simultaneously. These findings indicate that improving students' understanding and technical skills plays an important role in shaping readiness and awareness to face digital transformation in the field of accounting. This research provides theoretical contributions in the development of digital accounting studies as well as practical implications for educational institutions in designing curricula and learning that are relevant to the needs of the accounting profession in the technological era